Utopophobia : on the limits (if any) of political philosophy - Estlund, David M. (Princeton University Press, 2020)
"Throughout the history of political philosophy and politics more broadly a debate has raged about the proper place of idealism versus realism in our thinking about political principles and institutions. Within contemporary political philosophy, this debate has taken the form of what is called "ideal theory" versus "non-ideal theory." Non-ideal theorists have tried to shift the focus of political philosophy from theorizing about the nature of concepts like "justice" to questions about which feasible institutional and political changes would make a society, or the world, more just. But what if, the ideal theorist asks, justice is a standard that no society is likely ever to satisfy? Could we somehow even know this is the case before seriously considering what justice requires? And, if social justice were unrealistic, would that mean that understanding justice is without value or importance, and merely idle utopianism? In Utopophobia, David Estlund argues that the best reasons for thinking either that justice must be realistic, or for thinking that there is no point in understanding justice unless it could be realized, are not convincing. No particular theory of justice is offered or presupposed by Estlund in this book, nor is it argued that justice is indeed unrealizable-only that it could be, and that this possibility upsets common ways of proceeding in political thought. The book, thus, represents a critical engagement with important strands in traditional and contemporary political philosophy which suppose that a sound theory of justice, or even the enterprise of political philosophy generally, has the sole or overriding and defining task of contributing practical guidance toward greater social justice. Along the way, Estlund argues against several tempting views; that the "circumstances of justice," as understood by Hume and Rawls, imply that the very idea of social justice is grounded in unfortunate but realistic conditions of individual moral deficiency; that inquiry in political philosophy could have significant value only insofar as it guides to practical political action; and that understanding true justice would necessarily have practical value, at least as an ideal arrangement to be approximated"--